COMPARISON BETWEEN METABOLIC PARAMETERS, FOOD INTAKE, AND GUT MICROBIOTA IN TYPE 2 DIABETES AND NON-DIABETIC INDONESIAN WOMEN - Ninik Rustanti; Agnes Murdiati; Mohammad Juffrie; Endang Sutriswati Rahayu (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2023)
ABSTRACTBackground: Globally, the increasing incidence of type 2 diabetes mellitus (T2D) has resulted in an upsurge in research into this metabolic condition. Women, particularly in Indonesia, have a greater risk of T2D than males. The diversity of the gut microbiota (GM) in T2D is regulated by the number of carbs, protein, fat, and fiber consumed. Objectives: This study examined the comparison between metabolic parameters, food intake, and GM in T2D and non-diabetic Indonesian women.Materials and Methods: The cohort study included people who did not have T2D and those who did. On day 28 of observations, anthropometric, metabolic parameters, food intake, physical activity, and feces were collected. Feces were collected for pH, SCFA, and GM (L. plantarum, Bifidobacterium, and Prevotella) analysis. Results: There were significant differences between non-diabetic and diabetic women in age, Waist Hip Ratio (WHR), fasting blood sugar (FBS), and HbA1c. The two groups did not differ significantly in terms of their macronutrient intake (calories, carbs, protein, and fat), total water, and dietary fiber. Fecal pH and GM did not statistically differ between the control and T2D groups. Fasting blood sugar and HbA1c were positively associated with age, duration of T2D, WHR, and total water consumption, but slightly negatively associated with dietary fiber intake. Fasting blood sugar  was also slightly negatively associated with Prevotella, meanwhile HbA1c with Bifidobacterium. Carbohydrate intake were positively correlated with acetic, propionic, and butyric acid levels.Conclusion: Macronutrient intake, fecal pH, SCFA, and GM did not differ because GM in T2D increased bacause metformin consumption so that SCFA similar between two group. Keywords : food, gut microbiota, short-chain fatty acid,  diabetes, women